Phase transfer of 1- and 2-dimensional Cd-based nanocrystals. Issue 45 (4th November 2015) - Kodanek, Torben; Banbela, Hadeel M.; Naskar, Suraj; Adel, Patrick; Bigall, Nadja C.; Dorfs, Dirk
Abstract : 1- and 2-dimensional luminescent CdSe–CdS nano-heterostructures were successfully transferred into aqueous phase via ligand exchange with bifunctional thiol-based molecules. Abstract : In this work, luminescent CdSe@CdS dot-in-rod nanocrystals, CdSe@CdS/ZnS nanorods as well as CdSe–CdS core–crown nanoplatelets were transferred into aqueous phase via ligand exchange reactions. For this purpose, bifunctional thiol-based ligands were employed, namely mercaptoacetic acid (MAA), 3-mercaptopropionic acid (MPA), 11-mercaptoundecanoic acid (MUA) as well as 2-(dimethylamino)ethanthiol (DMAET). Systematic investigations by means of photoluminescence quantum yield measurements as well as photoluminescence decay measurements have shown that the luminescence properties of the transferred nanostructures are affected by hole traps (induced by the thiol ligands themselves) as well as by spatial insulation and passivation against the environment. The influence of the tips of the nanorods on the luminescence is, however, insignificant. Accordingly, different ligands yield optimum results for different nanoparticle samples, mainly depending on the inorganic passivation of the respective samples. In case of CdSe@CdS nanorods, the highest emission intensities have been obtained by using short-chain ligands for the transfer preserving more than 50% of the pristine quantum yield of the hydrophobic nanorods. As opposed to this, the best possible quantum efficiency for the CdSe@CdS/ZnS nanorods has been achieved via MUA. The gained knowledge could be applied to transfer for the first time 2-dimensional CdSe–CdS core–crown nanoplatelets into water while preserving significant photoluminescence (up to 12% quantum efficiency).